Transitioning to 100% Tobacco-Free: Perspectives from a Jesuit University - Bartos, Susan; Donoghue, Karen; Kelley, Patrick (Building Healthy Academic Communities Journal, 2017)
Aim: The purpose of this study is to examine the current social climate around tobacco at a Jesuit University and begin implementation procedures to transition the campus to a 100% tobacco free environment in a manner consistent with Jesuit and personal values. Background: Smoke-free campus policies are shown to be successful in reducing the amount of smoking and exposure to second-hand smoke. A comprehensive policy which includes traditional cigarettes, e-cigarettes, smokeless products, and hookah is recommended to eliminate the cultural acceptance of all tobacco products. Methods: A web-based survey was conducted following feedback from student led focus groups. Results: The majority of students (71%) agreed or strongly agreed with a transition to a tobacco-free policy with only 18% of the participants reporting negative feelings towards the policy change. Slightly more than half of the sample (53%) reported having a knowledge deficit related to available smoking cessation resources. Conclusions: There is an important balance between individual freedoms and upholding core Jesuit values in caring for the whole person. When implementing a new tobacco-policy, the current social climate, educational and cessation resources, and policy enforcement should be considered.